Some new approaches for prevention of schizophrenia spectrum disorders in patients exposed to exogenous stressors - Dzeruzhinska, Nataliya; Martsenkovsky, Igor; Kramar, Julia (Psychosomatic Medicine and General Practice, 2017)
Background. Environment factors affect to the clinical phenotype of schizophrenia spectrum disorders. Aim. To develop recommendations for the prevention schizophrenia spectrum disorders considering the influence of environmental factors on the clinical pathomorphosis of the disease. Methods. It was conducted the psychopathological and psychodiagnostic survey of 186 patients with schizophrenia spectrum disorders with an assessment of clinical features and level of social functioning. It was identified factors that have the most significant pathological effects on the course of disorders on the basis of the received data: the using of a cannabinoid in a family history, mother`s infectious and somatic diseases during pregnancy, mother’s using alcohol during pregnancy, consumption of alcohol in adolescent patients, fetal hypoxia or perinatal trauma of the patient at birth, problems with the group of primary support in the family of a child in childhood, maternal toxicosis, crisis relationships in the family, migration to different cultural environment. Results. Clinical pathomorphism of disorders of the spectrum of schizophrenia under the influence of environmental factors determines the features of psychotherapeutic interventions. In people with cannabinoids, it is important to eliminate the symptoms of anxiety through emotion-supportive measures, as well as to create a motivation to ask help in case of symptoms of schizophrenia spectrum disorders. In a group with perinatal complications, the emphasis should be put on cognitive methods in order to correct mental disorders and overcome hypochondria. Early measures to form a positive attitude towards themselves and the environment, supporting family relationships, overcoming depressive symptoms, and developing social activity are targets of psychotherapeutic interventions in people with schizophrenic spectrum disorders and psychological traumatic events. Conclusion. Minimization of environmental factors influence in high-risk individuals would postpone early manifestation, reduce disability in patients with schizophrenia spectrum disorders, as evidenced by the statement of leading health experts.